ANALISIS POTENSI KOMODITAS UNGGULAN PADA KAWASAN MINAPOLITAN DALAM UPAYA PENINGKATAN PEREKONOMIAN KABUPATEN SIDOARJO - Fransisca Bella Angela Putri; Arief Bachtiar (Al-Buhuts, 2024)
This research aims to analyze superior commodities found in the Minapolitan area in an effort to improve the economy in Sidoarjo Regency. This analysis uses secondary data from 2018 - 2022 obtained from the annual report of the Maritime and Fisheries Service of Sidoarjo Regency, with data analysis using Location Quotient (LQ) Analysis, Dynamic Location Quotient (DLQ) Analysis, Klassen Typology, Shift Share, while in determine related strategies for developing superior aquaculture commodities using SWOT Analysis. The results of the research show that superior and prospective commodities in the Minapolitan area include milkfish, tiger prawns, vaname shrimp, tilapia, white shrimp, fire shrimp, rebon shrimp, tilapia, white snapper, keting, crab and freshwater tilapia, so that in the classification of commodities It is included in quadrant 1 in the Klassen Typology chart. On the other hand, commodities that are experiencing rapid growth and are competitive include tilapia and freshwater tilapia, and these commodities are included in quadrant 1 in the Shif Share analysis chart. In the development of aquaculture, the chosen strategy is determined as a priority scale for development, namely the development of technology-based innovation, training in processing superior seeds, utilizing marketplaces and social media marketing, increasing the added value of the commodities produced, creating regulations that facilitate the distribution of commodity products